Continuing Education as a Condition of the Modern Teacher Professional Development - Korjakovceva, Olga; Tarhanova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article discusses the professional development of the teacher as the main condition for the effectiveness of educational process in higher school. The basis of the professionalism of the teacher, the author considers the psycho-pedagogical competence, it reveals the types and defines their role in the process of learning management students. In the framework of the system of additional professional education of the University presents the possible stages in the development of psycho-pedagogical competence, offers innovative approaches to the organization of continuous professional education of teachers.